LIVER TRANSPLANTATION AFTER SEVERE HEPATIC TRAUMA: CURRENT INDICATIONS AND RESULTS - RIBEIRO-JR,Marcelo Augusto Fontenelle (2015)
Background: The liver is the most injured organ in abdominal trauma. Currently, the treatment in most cases is non-operative, but surgery may be necessary in severe abdominal trauma with blunt liver damage, especially those that cause uncontrollable bleeding. Despite the damage control approaches in order to achieve hemodynamic stability, many patients develop hypovolemic shock, acute liver failure, multiple organ failure and death. In this context, liver transplantation appears as the lifesaving last resource Aim: Analyze the use of liver transplantation as a treatment option for severe liver trauma. Methods: Were reviewed 14 articles in the PubMed, Medline and Lilacs databases, selected between 2008-2014 and 10 for this study. Results: Were identified 46 cases undergoing liver transplant after liver trauma; the main trauma mechanism was closed/blunt abdominal trauma in 83%, and severe trauma (>grade IV) in 81 %. The transplant can be done, in this context, performing one-stage procedure (damaged organ removed with immediate transplantation), used in 72% of cases. When the two-stage approach is performed, end-to-side temporary portacaval shunt is provided, until new organ becomes available to be transplanted. If two different periods are considered - from 1980 to 2000 and from 2000 to 2014 - the survival rate increased significantly, from 48% to 76%, while the mortality decreased from 52% to 24%. Conclusion: Despite with quite restricted indications, liver transplantation in hepatic injury is a therapeutic modality viable and feasible today, and can be used in cases when other therapeutic modalities in short and long term, do not provide the patient survival chances.